PENDAMPINGAN GIZI REMAJA PUTRI DALAM PENCEGAHAN ANEMIA DI WILAYAH KERJA PUSKESMAS SIDOMULYO - Dewi Erowati; Yolahumaroh Yolahumaroh; Yessi Marlina (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2023)
Poor consumption behavior in adolescence, such as diet trends and consumption of junk food, is the underlying cause of the emergence of various nutritional problems. Protein along with iron (heme) plays a role in the transportation of nutrients by forming a complex of hemoglobin in the body. If the body is deficient in protein, it can interfere with the formation of hemoglobin. The program for giving iron supplements to adolescence women in the working area of the Sidomulyo Health Center has been running but due to the Covid-19 pandemic and the implementation of online teaching and learning activities (students are not present at school) it has stopped since 2019. So it is necessary to provide assistance in giving iron supplements and accompanied by nutrition education in order to prevent the incidence of anemia in adolescent womens in Pekanbaru City High School. The purpose of this Community Service is to provide assistance for adolescent womens to consume iron and nutrition education. The result of this community service is an increase in adolescent nutritional knowledge and adherence to consuming iron suplements. Nutrition education for adolescent womens was provided with the counseling method and the " Adolescent Womens’ Nutrition Diary" module and there was an increase in the nutritional knowledge score of adolescent womens  before receiving education, namely 67.38% and after receiving education 85.71%. In addition, a quiz competition was held in order to measure the level of understanding of nutrition education that had previously been carried out. Mentoring is done by holding a “Together Consuming Iron Supplements” so that the iron supplements given is guaranteed to be 100% consumed by adolescent womens. Learning nutrition for adolescent womens in preventing anemia can continue for a long time to form educational networks through Instagram media. Key word : Macro Nutrient Intake, Iron Supplements, Anemia in Adolescent Womens